Study of Viruddha Aahar in Healthcare Management - Vijay Kumar; Vijay Shankar Pandey (AYUSHDHARA, 2023)
Viruddha Aahar or incompatible diet is very important issue discussed by ancient Ayurveda scholars. Viruddha Aahar is certain diet and its combinations which interrupts the metabolism of tissue, which inhibits the formation of tissue and which have the opposite property to the tissue. Charak has mentioned many diseases due to Viruddha Aahar as- infertility, fistula-in-ano, anemia, leprosy, defective birth etc. and death too. In Ayurvedic literatures many incompatible food has mentioned, but we have to identify new food incompatibilities which are used frequently in modern society. eg.- green or black tea and milk. Tea contains flavonoids called catechins, which have beneficial effect on heart, but when mixed with milk, group of proteins in milk called Caseins, interact with the tea to reduce the concentration of catechins. Treatment of diseases, induced or produced due to Viruddha Aahar, is explained in Charak Samhita. According to Charak, Samshodhan and Samshaman Chikitsa is useful for such diseases followed by regular use of Rasayana for long period.